2014
DOI: 10.1002/btpr.1979
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of aqueous two‐phase systems and three‐phase partitioning for the recovery of superoxide dismutase from a clarified homogenate of Kluyveromyces marxianus

Abstract: Superoxide dismutase (SOD; EC 1.15.1.1) is an antioxidant enzyme that represents the primary cellular defense against superoxide radicals and has interesting applications in the medical and cosmetic industries. In the present work, the partition behavior of SOD in aqueous two-phase systems (ATPS) (using a standard solution and a complex extract from Kluyveromyces marxianus as sample) was characterized on different types of ATPS (polymer-polymer, polymer-salt, alcohol-salt, and ionic liquid (IL)-salt). The syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Although IL-based ABS were among the two systems that allowed better enzyme recovery, the authors concluded that the PEG3350-potassium phosphate ABS was better in terms of SOD recovery, enzyme specific activity maintenance, and purification. 259 …”
Section: Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although IL-based ABS were among the two systems that allowed better enzyme recovery, the authors concluded that the PEG3350-potassium phosphate ABS was better in terms of SOD recovery, enzyme specific activity maintenance, and purification. 259 …”
Section: Proteinsmentioning
confidence: 99%
“…Although IL-based ABS were among the two systems that allowed better enzyme recovery, the authors concluded that the PEG3350-potassium phosphate ABS was better in terms of SOD recovery, enzyme specific activity maintenance, and purification. 259 Further applications of IL-based ABS in the purification of enzymes include the extraction of wheat esterase from wheat extracts. 260 This enzyme can substitute the traditional acetylcholinesterase (AChE) extracted from animal blood or tissues.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…One example is the successful pioneering work of Hayenga et al on chymosin purification [94]. Other examples include: (i) separation of plasmid DNA from mRNA and tRNA [73]; (ii) simultaneous extraction and purification of lectins from plant extracts [95]; (iii) purification of human growth hormone from a fermentation broth [18]; (iv) purification of recombinant human serum albumin from viscous fermentation feed [50]; (v) purification of enzymes such as superoxide dismutase [96] and laccases [58, 97] from fermentation feeds; and (vi) extraction and purification of retamycin [14] and tetracycline [98] direct from fermentation broth.…”
Section: Opportunities – Atps Partitioning In Relation To Other Modmentioning
confidence: 99%